Influence of pacifier design on pacifier-palate contact: a finite element analysis - Michaela Maintz; Prasad Nalabothu; Florian M. Thieringer; Carlalberta Verna (Head & Face Medicine)
Abstract Objective The study compares the contact pressure and pressure distribution of various pacifier shapes on the palatal surfaces of newborns and six-month-old infants using nonlinear finite element analysis (FEA). Additionally, it seeks to assess the extent and pattern of interaction between pacifier designs and the lateral and medial zones of the palates. Materials and methods 3D finite element models of four pacifiers (A = NUK®, B = MAM®, C = BIBS®, D = CURAPROX®) of newborn and six-month-old palate and tongue were developed. The palate geometries were based on dental stone impressions of a neonate and six-month-old infant. The pacifier designs were digitized using computed tomography and analyzed in ANSYS Mechanical 2024 R1 (Ansys, Inc., Canonsburg, USA). Hyperelastic silicone rubber properties were used, while the palate and tongue were modeled as rigid and the mucosa as flexible. The interaction between different pacifier designs and the palate of a newborn was assessed through deformation, contact area, and contact pressure relative to the vertical tongue displacement in the anterior, medial, and lateral zones of the palates. Results Pacifier D exhibited the highest lateral and medial pressures on both the newborn and six-month-old palates with its broad-winged design. Pacifiers A and B showed moderate but steady increases in lateral pressure. In contrast, pacifier C showed concentrated pressure in the anterior zone with its distinct, rounded shape, particularly on the newborn palate. Pressure distribution patterns differed significantly between pacifier designs, with pacifier D showing the most extensive and uniform pressure distribution across the palate. Conclusions Pacifier design significantly influences palatal interaction, with broader shapes resulting in higher pressure concentrations on the lateral sides that may affect the transversal palate dimension. Understanding the biomechanical impacts of pacifier use is the first step in giving valuable insights to both clinicians and parents in making informed decisions regarding pacifier selection to support optimal oral development. Further clinical studies are needed to validate these findings.